Thymoquinone-loaded PLGA nanoparticles: antioxidant and anti-microbial properties - Nallamuthu, Ilaiyaraja; Parthasarathi, Ambica; Khanum, Farhath (International Current Pharmaceutical Journal, 2013)
The aim of the present study was to synthesize and characterize the Thymoquinone (TQ) encapsulated PLGA (poly (dl-lactide-co-glycolide) nanoparticles, and further evaluate for its antioxidant and anti-bacterial activities. TQ is a potential active ingredient of Nigella sativa seed and possess a spectrum of therapeutic properties. Nanoparticles were prepared according to solid-in-oil-in-water (s/o/w) solvent evaporation method. Dynamic laser light scattering (DLS) and SEM studies indicated a mean particle size of < 200 nm. The success of encapsulation was confirmed by FTIR technique, and the encapsulation efficiency (EE) of TQ was determined to be 62%. In vitro drug release study showed a maximum release of TQ at 75% and 54 % respectively for artificial intestinal and gastric juices over the period of 7 days. DPPH radical scavenging activity of the nanoparticles was found to be 71% at 1 mg/ml concentration. It also exhibited antibacterial property against E. coli, Staphylococcus aureus and Salmonella typhi strains, tested using well diffusion method. In conclusion, our study shows that PLGA encapsulated TQ nanoparticle with sustained release property has preserved antioxidant as well as anti-microbial activity, and therefore suggesting its therapeutic applications in various food samples. DOI: http://dx.doi.org/10.3329/icpj.v2i12.17017 International Current Pharmaceutical Journal, November 2013, 2(12): 202-207